Broken trail - Parks, Van Dyke 1943- (Sony Pictures Home Entertainment, 2009)
A man and his estranged nephew become the guardians of five abused and abandoned Chinese girls. Their rivals intend to kidnap the girls while the two are delivering a herd of horses